Effect of microwave-assisted extraction on the yield and quality of apple pomace and lemon peel pectins - Zarei, Mohammad; Ahmadi Zenouz, A.; Saari, Nazamid; Ghanbari, R.; Nikkhah, M.; Vaziri, M. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Microwave assisted extraction treatments showed the higher pectin yields of 10.07% and 8.83% in pretreated samples by microwave and 9.4% and 8% in the extraction of dried after microwave treatment in lemon peel and apple pomace samples, respectively. Lemon peel pectin in pretreated samples by microwave and extraction of dried after microwave treatment showed the higher degree of esterification 71.8% and 70%, respectively, while apple pomace revealed 68% and 65.4% in same treatments. Furthermore, lemon peel pectin exhibited the highest galacturonic content of 74.5% in extraction of pretreated samples by microwave, while apple pomace pectin indicated the higher galacturonic acid content of 70.5% and 70% in both extraction of dried after microwave treatment and extraction of dried samples. Texture analysis of jellies prepared by various extracted pectin indicated the highest fracturability in the microwave-assisted drying treatment of 33 N and 32.5 N for apple pomace and lemon peel pectin, respectively.